2013
DOI: 10.3109/09593985.2013.816399
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic girdle pain in Indian postpartum women: a cross-sectional study

Abstract: We found a high prevalence of PGP in Indian women during the first three months of postpartum period. Our finding suggests that unilateral posterior pelvic pain provocation test (P4), ASLR test score ≥4, caesarean section delivery and sitting in breast-feeding posture were associated with increased risk of PGP during postpartum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 51 publications
1
19
0
Order By: Relevance
“…Pelvic girdle pain (PGP) is a universal problem affecting approximately 50% of all pregnant women [1,2] regardless of socioeconomic factors [3][4][5][6][7] . It is a musculoskeletal pain located within the pelvic area between the posterior iliac crest and gluteal folds, with or without leg pain [8] .…”
Section: Introductionmentioning
confidence: 99%
“…Pelvic girdle pain (PGP) is a universal problem affecting approximately 50% of all pregnant women [1,2] regardless of socioeconomic factors [3][4][5][6][7] . It is a musculoskeletal pain located within the pelvic area between the posterior iliac crest and gluteal folds, with or without leg pain [8] .…”
Section: Introductionmentioning
confidence: 99%
“…Only 9% reported improvement after discontinuing breastfeeding, whereas 22% reported an exacerbation of the pain after discontinuation. Conversely, a cross‐sectional study of 284 Indian women 3–18 months after delivery reported that neither patterns nor duration of breastfeeding were related to pelvic girdle pain …”
Section: Discussionmentioning
confidence: 97%
“…A follow‐up study of 464 Swedish women with lumbopelvic pain during pregnancy reported a positive association between breastfeeding and persistent pain at 6 months after delivery . In contrast, no association between breastfeeding and pelvic girdle pain 3–18 weeks after delivery was found in a cross‐sectional study of 284 Indian women …”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations